Book review: Glazyev, S. Yu., Andronova, I. V., Kamalyan, A. K., & et al. (Eds.). (2023). Eurasian Economic Integration: Theory and Practice: Textbook. Moscow: Prospekt publ., 648 p. (In Russian) - Igor A. Filkevich; Jianwei Zhang (Vestnik RUDN. International Relations)
-